Issues and problem related to the teaching of psychology and training of professional psychologists - Abdul Halim Othman, 1938-; Wan Rafaei Abdul Rahman; International Conference on the Role of Universities in Developing Nations (1980 : Universiti Kebangsaan Malaysia) ([s.-l. : s.-n.], 1980)
32